2018
DOI: 10.4314/aas.v14i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Early Bacterial Cultures from Open Fractures - Differences Before and After Debridement

Abstract: Background: The pattern of organisms found in open fractures is important in the selection of antibiotics for prophylaxis and empirical treatment. So far, there is paucity of data on local patterns of bacteria contaminating and infecting open fractures and their antibiotic susceptibility profile. Objective: To describe the pattern and antibiotic susceptibility of bacterial isolates obtained within 24 hours of injury from open fractures and to compare these to bacterial isolates from fractures that subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
5
7
2
1
Order By: Relevance
“…9 In our study, most of bacterial infections in open fracture wounds were caused by gram-negative organisms (80.3%) with Pseudomonas and Klebsiella were the most predominant gram negative isolates. These findings are consistent with those found by Sitati et al 11 In the present study, Staphylococcus aureus was found to be predominant gram-positive isolates. Mangala et al and Bhatty et al noticed the same thing.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…9 In our study, most of bacterial infections in open fracture wounds were caused by gram-negative organisms (80.3%) with Pseudomonas and Klebsiella were the most predominant gram negative isolates. These findings are consistent with those found by Sitati et al 11 In the present study, Staphylococcus aureus was found to be predominant gram-positive isolates. Mangala et al and Bhatty et al noticed the same thing.…”
Section: Discussionsupporting
confidence: 94%
“…However, these drugs are costly and not to be recommended for prophylaxis to protect their efficacy. In our study, grampositive organisms also showed high susceptibility to 3 rd generation cephalosporins (cefotaxime 78.8%) and these findings are consistent with those found by Sitati et al 11 In the present study, amikacin and ciprofloxacin were found to be the most effective antibiotics against the tested gram-negative organisms except Citrobacter and these findings are consistent with those found by Sitati et al and Agarwal et al 9,11…”
Section: Discussionsupporting
confidence: 92%
“…Local studies at our hospital by Ondari et al (2016) and Sitati et al (2017) showed a higher overall proportion of gram positive than gram negative isolates, with S. aureus being the most predominant. Our results were different from these two studies.…”
Section: Discussionmentioning
confidence: 74%
“…Further contamination occurs in the course of management at the hospital. A study done to determine if organisms isolated from wounds before initial debridement are similar to those causing infection after debridement found that the isolates were not similar and that infections were mainly caused by nosocomial microorganisms (Sitati et al, 2017). The profile of microbial isolates in infected open fractures may vary from one health institution to another and from time to time.…”
Section: Introductionmentioning
confidence: 99%
“…La toma de cultivos antes de la limpieza quirúrgica puede resultar en el tratamiento antibiótico innecesario. Dos estudios recientes han demostrado que los cultivos tomados superficialmente no predicen la infección de la herida en el período posoperatorio, ya que los microrganismos aislados en ellos difieren de aquellos obtenidos de la herida una vez que la misma presenta signos de infección (47,48).…”
Section: ) Tratar Solo Las Infecciones No Colonizaciones Ni Contaminacionesunclassified